Math, asked by divyanshusinghrana84, 9 months ago

(3/5)^2×(-1/-3)^3×2^3​

Answers

Answered by IIMidnightHunterII
1

Answer:

 =  {( \frac{3}{5}) }^{2}  \times  { (\frac{ - 1}{ - 3} )}^{3}  \times  {2}^{3}  \\  \\  =  \frac{ {3}^{2} }{ {5}^{2} }  \times   \frac{ { - 1}^{3} }{  { - 3}^{3} }  \times 8 \\  \\  =  \frac{9}{25}  \times  \frac{ - 1}{ - 27}  \times 8 \\  \\  =  \frac{9}{25}  \times  \frac{1}{27}  \times 8 \\  \\  =  \frac{1}{25}  \times  \frac{1}{3}  \times 8 \\  \\   = \frac{8}{75}

Answered by AnonymousLearns
0

Answer in the photo.

Whenever you are swayed away by the scaring exponent symbol, remember it's just repeated multipilcation and is just as simple as that.

Attachments:
Similar questions